Texas history - Buenger, Walter L.; Zamora, Emilio (Pearson, 2016)
Natural Texas and its people (prehistory-1500s) -- The age of contact (1492-1689) -- The Spanish colonial and Mexican national eras (1690-1835) -- Revolution and republic (1827-1845) -- Early statehood, civil war, and reconstruction (1845-1876) -- Cotton, cattle, railroads, and the age of oil (1865-1930) -- Texas in the Great Depression and World War II (1900-1945) -- Era of civil rights and conservatism (1945-present) -- Contemporary Texas (1980s-present) -- United States Constitution -- Primary sources -- Declaration of Independence -- 21st century skills -- Atlas -- Glossary